Constraints in Adoption of Various Dairy Animal Management Practices in the Coastal Area of South Gujarat - Singh, Rana Ranjit; Chaudhary, Sandhya; Patel, NB; Singh, Virendra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A field survey was conducted to collect the information on constraints faced by dairy animal owners of Navsari taluka of Navsari district of South Gujarat. Fifteen villages of Navsari taluka having functional primary milk producer’s co-operative societies were selected. Ten dairy animal owners from each selected village were randomly chosen which constituted a total of 150 respondents. The selected farmers were interviewed and the preferred information was collected with the help of predesigned and pretested questionnaire. Perusal of data revealed that major constraint faced by the dairy animal owners in providing adequate housing to their dairy animals was lack of own capital. Major constraints in adopting recommended feeding practices were high cost of feed and non-availability of green fodder round the year. Lack of knowledge of heat detection and lack of improved bulls for breeding in villages were major constraints in adopting proper animal breeding practices, while inadequate knowledge of diseases and their control was major constraint in adopting proper health care management practices.
Keywords: Constraints; Dairy Animals; Housing; Breeding; Feeding; Coastal Gujarat